The Role of the Just Energy Transition Partnership (JETP): Between Commitment and Implementation - Nur, Usi Alfiani; Bainus, Arry; Darmawan, Wawan Budi (Yayasan Ilomata, 2025)
Climate change necessitates a global shift toward sustainable energy, prompting international initiatives such as the Just Energy Transition Partnership (JETP) to bridge the gap between global climate commitments and national development priorities. This study examines Indonesia's international role realization through JETP implementation within a hybrid global governance framework, utilizing role performance theory to analyze the alignment between partnership commitments and actual implementation outcomes. Employing qualitative research methods with systematic literature review spanning 2022-2025, this research investigates JETP's USD 20 billion commitment through a dual-level analysis encompassing international partnership dynamics and domestic policy translation mechanisms. The findings reveal a significant gap between ambitious commitments and implementation realities, with only USD 1.1 billion (5.5%) mobilized through 54 projects by September 2024. While JETP successfully established multi-stakeholder coordination mechanisms involving G7 countries, international financial institutions, and Indonesia's national framework, operational challenges, including complex disbursement processes, extended stakeholder consultations, and structural limitations in financing architecture, have hindered rapid implementation. This research contributes to understanding the intersection of symbolic commitment and structural barriers in international environmental governance, demonstrating that multilateral climate finance partnerships require substantial institutional maturation time to effectively bridge global climate goals with national energy transition realities in developing countries.